Antimicrobial strategies in the care of organ transplant recipients. - Rubin, R H (1993)
Since the early days of transplantation, infection has been a major consequence of antirejection immunosuppressive therapy. Increasingly effective prophylactic and preemptive strategies are being developed to prevent the infectious consequences of immunosuppressive therapy. Although the data base is incomplete and there remains a compelling need for well-designed, randomized, comparative trials, the potential for controlling life-threatening viral, bacterial, fungal, and protozoal infections exists. The cornerstone of this effort is the recognition that effective immunosuppressive strategies require an antimicrobial program to make them safe and that such an antimicrobial program needs to be individualized in order to be appropriately matched with the needs of the antirejection program. Thus, escalation and de-escalation of the antimicrobial program should be carried out to match the immunosuppressive program. Infection and rejection remain closely intertwined, linked by the immunosuppressive program that is prescribed.